Experimental studies of basalt-H2O-CO2 interaction with a high pressure column flow reactor: the mobility of metals - Galeczka, I.; Wolff-Boenisch, Domenik; Gislason, S. (Elsevier, 2013)
Here, we report on the mobility of metals at the early stage of CO2 injection into basalt, before significant precipitation of secondary minerals. Short-lived pulses (50-100 hours) of CO2-charged water were injected into a high pressure column flow reactor filled with basaltic glass grains at 22°C, 8 MPa of total pressure and a velocity of 0.4 cm/min. The residence time of the water within the column ranged from 8 to 10 hours. The column was conditioned with pure water, resulting in alkaline outflow (pH ~9). The pH of the inlet CO2-charged water was ~3.2, and the lowest pH measured in the column was 4.5, after less than 10 hours of water/rock interaction. The dissolved metal concentrations and metals relative mobility increased dramatically during the CO2-pulses; more than 100 times for Sr, Fe, Al, Ca, Ba, Mn, and Mg. Of these elements, all but Al can bind with CO2 to form carbonate minerals. Only the dissolved Al, Fe, Mn and Cr concentrations exceeded allowable drinking water limits. After the CO2-pulses, all of the elemental concentrations decreased close-to or even below what was measured during the conditioning of the column. The pH never reached ~9 which was the initial pH before CO2-pulses.